Anodized aluminum substrate and preparation method thereof
By optimizing the chemical composition and process of aluminum alloys, the problems of rough grains and high production costs in the anodized process of traditional aluminum alloys are solved, and the fluidity, tensile strength and corrosion resistance of the anodized aluminum substrate are improved, so as to achieve Higher dimensional accuracy and surface quality.
Patent Information
- Application Number
- CN202211611179.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-12-15
AI Technical Summary
During the anodizing process, traditional aluminum alloys have a rough surface of the alumina film due to large grains, and the particles are prone to fall off. The production cycle is long and the manufacturing cost is high. The high Mg content limits its application in the field of high conductivity and high heat dissipation.
By optimizing the chemical composition of aluminum alloys, adding specific proportions of manganese, titanium, strontium and rare earth elements, adjusting the weight ratio of silicon to aluminum, and using three-pass cold rolling and high-temperature rapid annealing method to optimize the flowability of anodized aluminum substrate. and anodizing properties.
It improves the flowability and tensile strength of the anodized aluminum substrate, reduces the roughness of the film layer, enhances corrosion resistance, promotes the dimensional accuracy and surface quality of the product, and reduces casting defects.
Smart Images

Figure 92094DEST_PATH_IMAGE002 
Figure 112637DEST_PATH_IMAGE001
Abstract
Description
Technical Field
[0001] The invention relates to an anodized aluminum substrate, and in particular to an anodized aluminum plate and a preparation method thereof. Background Art
[0002] Aluminum alloy has high specific strength, low density, low cost, and good thermal conductivity. Aluminum alloy that can obtain a uniform and beautiful film appearance after being dyed with anodizing agent has great market demand in the application fields of 3C product shells and automotive parts. Different alloying elements in aluminum alloy will affect the organizational structure of the matrix, the properties, content and distribution of the second phase, and thus affect the quality of the anodized film. Therefore, the development of a new type of cast aluminum alloy with good fluidity and anodizing performance has great application prospects and market demand. Traditional aluminum alloys have strong mechanical strength, but the grains of aluminum alloys are large. When doing the anodized aluminum process, the surface of the aluminum oxide film is very rough, causing particles to fall off.
[0003] Patent application No. 201810889362.9 discloses a 6-series alloy anodized aluminum sheet strip for mobile phone frames and its preparation method. By adjusting the alloy elements, 390-410℃, 8-12 hours and 530~540℃, 30~40h long-term double-stage homogenization treatment, combined with 540~570℃, 1~2 hours long-term solution treatment, a high-strength product with a finished thickness of 4.0~10.0mm is finally obtained, but it faces the problems of long production cycle and high manufacturing cost. Patent application number CN201810098770.2 discloses a mirror-like anodized aluminum alloy rolled plate and a preparation method thereof. The raw materials for the preparation include Mg 2.2~4.5%, Cu 0.02~0.08%, Mn 0.01%, Cr 0.01%, Zn 0.01% and the remainder Al, so that it has good anodizing performance. However, the mass percentage of Mg added to the prepared raw materials is 2.2~4.5%, which is limited in the field of high conductivity and high heat dissipation.
[0004] Therefore, the present invention optimizes the chemical composition of the aluminum alloy to prepare an anodized aluminum substrate with good fluidity, excellent anodizing performance and good tensile strength. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present invention provides an anodized aluminum substrate, wherein the raw materials at least contain, by weight percentage: 0.8-1.6% manganese, 3-8% non-metallic elements, 0.1-0.3% titanium, 0.02-0.06% rare earth elements, 0.01-0.06% strontium, and the balance is aluminum.
[0006] As a preferred solution, the rare earth element is one or more of yttrium, scandium, lanthanum and praseodymium.
[0007] As a preferred solution, the rare earth element is scandium.
[0008] As a preferred solution, the non-metallic element is silicon.
[0009] As a preferred solution, the weight ratio of the non-metallic element to aluminum is 5:(93~94).
[0010] In the present invention, the applicant found that when the weight ratio of silicon to aluminum is 5: (93-94), the fluidity of the anodized aluminum substrate melt is effectively improved, and the tensile strength of the aluminum alloy is also improved. This may be because when a specific proportion of silicon is added, it can form a eutectic structure with the aluminum in the system, with a small solidification range and small flow resistance. Moreover, the added silicon can reduce the eutectic temperature of aluminum, and at the same casting temperature, it has a larger superheat, thereby improving the fluidity of the aluminum alloy during processing, thereby also improving the tensile strength of the aluminum alloy. However, when the weight ratio of silicon to aluminum is too large, a large amount of coarse silicon phase may exist in the alloy matrix, and the coarse silicon phase cannot be oxidized, which will hinder the continuous growth of the film layer and seriously affect the anodizing performance of the aluminum alloy.
[0011] As a preferred solution, the weight ratio of titanium to strontium is (0.1-0.3): (0.01-0.06).
[0012] As a preferred solution, the weight ratio of titanium to strontium is (0.1-0.3): (0.03-0.04).
[0013] The applicant has found through a large number of experiments that when the weight ratio of titanium and strontium is (0.1~0.3): (0.03~0.04), the grains can be refined, the fluidity of the anodized aluminum substrate melt can be improved, the roughness of the film layer can be effectively reduced, and the film layer can be made more uniform, and the corrosion resistance of the anodized film can also be improved. The applicant speculates that when titanium and strontium are added in a weight ratio of (0.1~0.3): (0.03~0.04), the microstructure of the anodized aluminum substrate changes, the grains transform from dendritic to equiaxed, and the overlap time between the grains is delayed, thereby improving the fluidity of the anodized aluminum substrate melt. At the same time, the grains are refined, which can effectively reduce the roughness of the film layer, make the film layer more uniform, and also improve the corrosion resistance. However, the applicant unexpectedly discovered that when the weight ratio of titanium to strontium is too large, its corrosion resistance will be greatly reduced. This may be because the increase of titanium element will lead to coarsening of grains, thus affecting the corrosion resistance. At the same time, when the melt solidifies, Al3Ti phase, Al3Sc phase and Al6Mn phase precipitate before α-Al phase to accelerate the solidification speed of the anodic oxide film substrate melt, thereby reducing fluidity. However, when the weight ratio of titanium to strontium is too small, the roughness of the film layer will increase significantly, and the quality of the film layer will deteriorate significantly.
[0014] A second aspect of the present invention provides a method for preparing an anodized aluminum substrate, the steps of which include:
[0015] (1) Preheating and smelting aluminum to obtain aluminum melt;
[0016] (2) Add manganese, titanium, scandium and strontium to the aluminum melt. After all of them are melted, stir them evenly to obtain an alloy melt.
[0017] (3) Degassing and heat preservation.
[0018] (4) Remove the slag, pour into a mold, cool to room temperature, and obtain an ingot.
[0019] (5) subjecting the ingot to homogenization heat treatment;
[0020] (6) preheating, heat-insulating, and hot-rolling the ingot after homogenization heat treatment to obtain an aluminum alloy coil;
[0021] (7) Cooling the aluminum alloy coil to a temperature of 30-60°C, cold rolling, and annealing;
[0022] (8) The annealed substrate is subjected to aging treatment to obtain an anodized aluminum substrate.
[0023] As a preferred solution, the smelting temperature in step (1) is 700-800°C;
[0024] As a preferred solution, the stirring speed in step (2) is 600-1000 r / min;
[0025] As a preferred solution, the specific implementation method of degassing in step (3) is: adding flux for degassing;
[0026] As a preferred solution, the amount of the flux added is 1.2-1.6wt% of the total mass of the alloy melt.
[0027] As a preferred solution, the flux is one or more of NaCl, NaF, KCl, Na2SiF6, Na3AlF6, and CaF2.
[0028] As a preferred solution, the flux is a mixture of NaCl, Na2SiF6, and Na3AlF6.
[0029] As a preferred solution, the weight ratio of NaCl, Na2SiF6, and Na3AlF6 is (1-3): (5-6): (2-4).
[0030] As a preferred solution, the insulation time in step (3) is 15 to 20 minutes;
[0031] As a preferred solution, in step (5), the temperature of the homogenization heat treatment is 530-580° C., and the time of the homogenization heat treatment is 8-10 hours.
[0032] As a preferred solution, the preheating temperature in step (6) is 500-530°C.
[0033] As a preferred solution, the insulation time in step (6) is 5 to 10 hours.
[0034] As a preferred solution, the hot rolling in step (6) is specifically implemented as follows: first pass: thickness before rolling is 15-20 mm, reduction is 1-2 mm, and thickness after rolling is 13-19 mm; second pass: thickness before rolling is 13-19 mm, reduction is 3-5 mm, and thickness after rolling is 8-15 mm;
[0035] The third pass: the thickness before rolling is 8~15mm, the reduction is 5~6mm, and the thickness after rolling is 2~10mm;
[0036] As a preferred solution, the temperature of the first, second and third hot rolling passes is 500-550°C.
[0037] As a preferred solution, the specific implementation method of the cold rolling is: the billet opening pass has a reduction of 25~30%, and a roller with a roughness of 0.5~0.8 is used for rolling; the intermediate pass has a reduction of 10~20%, and a roller with a roughness of 0.3~0.5 is used for rolling; the finished pass has a reduction of 20~30%, and a roller with a roughness of 0.1~0.3 is used for rolling.
[0038] As a preferred solution, the annealing temperature is 500-520° C., and the annealing time is 10-15 s.
[0039] The present invention adopts a three-pass cold rolling method, which enables the product to have higher dimensional accuracy, better version, high surface quality and uniform structure. However, due to the low temperature of cold rolling, dynamic recrystallization will not occur during the rolling process to produce work hardening, and a relatively high dislocation density is accumulated in the structure, thereby improving the strength and deformation resistance of the aluminum alloy, while accompanied by a decrease in plasticity, which is prone to brittle cracking. The applicant has found through a large number of experiments that when the annealing temperature is 500-520°C and the annealing time is 10-15s, the high-temperature rapid annealing method can be used to sharply reduce the dislocation density and strengthen the grains, so that the metastable state of the organization and performance caused by deformation can be eliminated and restored to a balanced state, thereby improving the toughness of the anodized film material. At the same time, the organization in the strip maintains the equiaxed grains, which helps to form a more uniform and beautiful anode surface after anodization.
[0040] As a preferred solution, the aging treatment is specifically implemented by keeping the temperature at 120-200°C for 10-15h.
[0041] The applicant found in the experiment that when the weight ratio of silicon to aluminum is (0.1~0.2):100, although the fluidity of the melt of the anodized aluminum plate substrate and the tensile strength of the anodized aluminum plate substrate can be improved, when the silicon content is too much, its toughness will deteriorate, that is, it greatly affects the performance of cold rolling. Therefore, the applicant found through a large number of experiments that when a specific three-pass hot rolling method with different reduction rates is adopted, the performance of cold rolling can be improved, thereby improving the dimensional accuracy of the anodized aluminum plate substrate, the version is better, the surface quality is high, and therefore has a uniform organization. The applicant speculates that after three passes of hot rolling, the cast structure has completely disappeared, the larger dendrites are broken, the grains are elongated to varying degrees along the rolling direction, and the brittle primary Si is evenly distributed in the plastic matrix after being broken, thereby improving the toughness of the anodized aluminum plate substrate. At the same time, the reduction amount after hot rolling continues to increase, and the more variable properties can be stored in the material, which is also beneficial to the recrystallization process during annealing.
[0042] Beneficial effects:
[0043] 1. The aluminum alloy prepared by the present invention has good fluidity, which is conducive to the floating of slag and the discharge of gas, reduces casting defects, and thus can obtain an anodized aluminum substrate with excellent performance;
[0044] 2. The present invention limits the weight ratio of titanium to strontium to (0.1-0.3): (0.01-0.06), which can refine the grains, improve the fluidity of the anodized aluminum substrate, effectively reduce the roughness of the film layer, make the film layer more uniform, and also improve the corrosion resistance of the anodized film.
[0045] 3. The present invention effectively improves the fluidity of the melt of the anodized aluminum plate substrate by limiting the weight ratio of silicon to aluminum to 5: (93-94), and also improves the heat dissipation performance and tensile strength of the anodized aluminum plate substrate, and the tensile strength is as high as 120MPa.
[0046] 4. The present invention adopts a specific three-pass cold rolling method and a high-temperature rapid annealing method, so that the product has higher dimensional accuracy, better version, high surface quality and uniform organization.
[0047] 5. The present invention improves the toughness of the anodized aluminum plate substrate by limiting the specific three-pass hot rolling method, and is also beneficial to the recrystallization process in the annealing stage. DETAILED DESCRIPTION
[0048] Example
[0049] Example 1
[0050] This embodiment provides an anodized aluminum substrate, wherein the raw materials include, by weight percentage, 1% manganese, 5% non-metallic elements, 0.2% titanium, 0.04% rare earth elements, 0.05% strontium, and the balance is aluminum.
[0051] The rare earth element is scandium. The non-metallic element is silicon.
[0052] In a second aspect of this embodiment, a method for preparing an anodized aluminum substrate is prepared, and the steps include:
[0053] (1) Preheating and smelting aluminum to obtain aluminum melt;
[0054] (2) Add manganese, titanium, scandium and strontium to the aluminum melt. After all of them are melted, stir them evenly to obtain an alloy melt.
[0055] (3) Degassing and heat preservation.
[0056] (4) Remove the slag, pour into a mold, cool to room temperature, and obtain an ingot.
[0057] (5) subjecting the ingot to homogenization heat treatment;
[0058] (6) preheating, heat-insulating, and hot-rolling the ingot after homogenization heat treatment to obtain an aluminum alloy coil;
[0059] (7) Cooling the aluminum alloy coil to 50°C, cold rolling, and annealing;
[0060] (8) The annealed substrate is subjected to aging treatment to obtain an anodized aluminum substrate.
[0061] The smelting temperature in step (1) is 750°C;
[0062] The stirring speed in step (2) is 800 r / min;
[0063] The specific implementation method of degassing in step (3) is: adding flux for degassing; the amount of the flux added accounts for 1.4wt% of the total mass of the alloy melt. The flux is a mixture of NaCl, Na2SiF6, and Na3AlF6. The weight ratio of NaCl, Na2SiF6, and Na3AlF6 is 2:5:3.
[0064] The insulation time in step (3) is 17 minutes;
[0065] In the step (5), the temperature of the homogenization heat treatment is 560° C., and the time of the homogenization heat treatment is 9 hours.
[0066] The specific implementation method of the hot rolling in step (6) is as follows: first pass: thickness before rolling is 18 mm, reduction is 2 mm, and thickness after rolling is 16 mm; second pass: thickness before rolling is 16 mm, reduction is 4 mm, and thickness after rolling is 14 mm; third pass: thickness before rolling is 14 mm, reduction is 6 mm, and thickness after rolling is 8 mm;
[0067] As a preferred solution, the temperature of the first, second and third hot rolling passes is 530°C.
[0068] The specific implementation method of the cold rolling is: the blanking pass has a reduction of 25%, using a roller with a roughness of 0.6; the intermediate pass has a reduction of 15%, using a roller with a roughness of 0.4; the finished pass has a reduction of 25%, using a roller with a roughness of 0.2.
[0069] The annealing temperature is 510° C., and the annealing time is 12 seconds.
[0070] The specific implementation method of the aging treatment is: keeping warm at 150° C. for 12 hours.
[0071] Example 2
[0072] This embodiment provides an anodized aluminum substrate, wherein the raw materials include, by weight percentage, 0.8% manganese, 5% non-metallic elements, 0.2% titanium, 0.06% rare earth elements, 0.06% strontium, and the balance is aluminum.
[0073] The rare earth element is scandium. The non-metallic element is silicon.
[0074] In a second aspect of this embodiment, a method for preparing an anodized aluminum substrate is prepared, and the steps include:
[0075] (1) Preheating and smelting aluminum to obtain aluminum melt;
[0076] (2) Add manganese, titanium, scandium and strontium to the aluminum melt. After all of them are melted, stir them evenly to obtain an alloy melt.
[0077] (3) Degassing and heat preservation.
[0078] (4) Remove the slag, pour into a mold, cool to room temperature, and obtain an ingot.
[0079] (5) subjecting the ingot to homogenization heat treatment;
[0080] (6) preheating, heat-insulating, and hot-rolling the ingot after homogenization heat treatment to obtain an aluminum alloy coil;
[0081] (7) Cooling the aluminum alloy coil to 50°C, cold rolling, and annealing;
[0082] (8) The annealed substrate is subjected to aging treatment to obtain an anodized aluminum substrate.
[0083] The smelting temperature in step (1) is 750°C;
[0084] The stirring speed in step (2) is 800 r / min;
[0085] The specific implementation method of degassing in step (3) is: adding flux for degassing; the amount of the flux added accounts for 1.4wt% of the total mass of the alloy melt. The flux is a mixture of NaCl, Na2SiF6, and Na3AlF6. The weight ratio of NaCl, Na2SiF6, and Na3AlF6 is 2:5:3.
[0086] The insulation time in step (3) is 17 minutes;
[0087] In the step (5), the temperature of the homogenization heat treatment is 560° C., and the time of the homogenization heat treatment is 9 hours.
[0088] The specific implementation method of the hot rolling in step (6) is as follows: first pass: thickness before rolling is 18 mm, reduction is 2 mm, and thickness after rolling is 16 mm; second pass: thickness before rolling is 16 mm, reduction is 4 mm, and thickness after rolling is 14 mm; third pass: thickness before rolling is 14 mm, reduction is 6 mm, and thickness after rolling is 8 mm;
[0089] As a preferred solution, the temperature of the first, second and third hot rolling passes is 530°C.
[0090] The specific implementation method of the cold rolling is: the blanking pass has a reduction of 25%, using a roller with a roughness of 0.6; the intermediate pass has a reduction of 15%, using a roller with a roughness of 0.4; the finished pass has a reduction of 25%, using a roller with a roughness of 0.2.
[0091] The annealing temperature is 510° C., and the annealing time is 12 seconds.
[0092] The specific implementation method of the aging treatment is: keeping warm at 150° C. for 12 hours.
[0093] Comparative Example 1
[0094] The specific implementation of Comparative Example 1 is the same as that of Example 1; the difference is that in Comparative Example 1, no non-metallic element is added to the anodized aluminum substrate.
[0095] Comparative Example 2
[0096] The specific implementation of Comparative Example 2 is the same as that of Example 1; the difference is that in Comparative Example 2, no strontium is added to the anodized aluminum substrate.
[0097] Comparative Example 3
[0098] The specific implementation method of Comparative Example 3 is the same as that of Example 1; the difference is that the specific implementation method of hot rolling in step (6) of Comparative Example 3 is: the final rolling temperature is 530°C, the thickness before rolling is 18mm, the rolling reduction is 10mm, and the thickness after rolling is 8mm.
[0099] Performance Testing:
[0100] The anodized aluminum substrates of Examples 1-2 and Comparative Examples 1-3 were processed as follows: (1) the workpieces were clamped with a fixture, and the polished samples were first ultrasonically cleaned in acetone for 10 min, then ultrasonically cleaned in anhydrous ethanol for 5 min, and finally cleaned with distilled water; (2) the samples were immersed in a 50 g / L NaOH solution at a constant temperature of 40°C in a water bath for 30 s, and then cleaned with distilled water; (3) the samples were pickled with a 200 g / L HNO3 solution for 2 min, and then cleaned with distilled water; (4) the cleaned samples were used as anodes and graphite sheets as cathodes, and placed in a 150 g / L sulfuric acid solution, and anodized at room temperature using a DC pulse power supply at a current density of 14 mA / cm -2 , the anodizing time is 30min. (5) First, immerse the sample in a 10g / L Na2S2O3 solution for 10min, and use a constant temperature water bath to maintain the temperature at 90℃. Then rinse the sample with distilled water for 30s. Then immerse the sample in a 10g / L KMnO4 solution for 5min, and use a constant temperature water bath to maintain the temperature at 90℃. Then rinse the sample surface with distilled water. Finally, place the sample in 100℃ distilled water for boiling water sealing treatment to obtain an anodized aluminum plate.
[0101] (1) Tensile strength: The anodized aluminum substrates obtained in Examples 1-2 and Comparative Examples 1-3 were subjected to tensile strength testing using a wire cutting machine. The size was cut according to ASTM E8M-04 standard. The instrument used was a SHIMADZU AG-X100KN universal testing machine. Each set of alloys was tested at a tensile speed of 1 mm / min and room temperature (25°C).
[0102] (2) Fluidity: The fluidity of the anodized aluminum substrate melt in Examples 1-2 and Comparative Examples 1-3 was tested by the spiral method. The mass of the anodized aluminum substrate was 500 g, and the pouring temperature was 760°C. After refining, degassing and slagging, the temperature-stable alloy melt was poured into a fluidity mold preheated to 200°C. After the alloy solidified and cooled, the mold was opened to measure the flow length.
[0103] (3) Roughness: The surface roughness of the anodized aluminum plates prepared in Examples 1-2 and Comparative Examples 1-3 was measured using a 3D surface morphology analyzer. The line scan speed was 200 point / mm, the line length was 10 mm, and 5 lines were selected on each of the two sides of the sample for measurement. The average roughness of the sample was calculated.
[0104] Performance test results:
[0105] Table 1 shows the performance test results of the anodized aluminum substrates prepared in Examples 1-2 and Comparative Examples 1-3.
[0106] Table 1
[0107]
[0108] Table 2 shows the performance test results of the anodized aluminum plates prepared in Examples 1-2 and Comparative Examples 1-3.
[0109] Table 2
[0110]
Claims
1. An anodized aluminum substrate, characterized in that: In terms of weight percentage, the raw materials include: 0.8-1.6% manganese, 3-8% non-metallic elements, 0.1-0.3% titanium, 0.02-0.06% rare earth elements, 0.01-0.06% strontium, and the balance is aluminum; The weight ratio of the non-metallic element to aluminum is 5:(93-94); the non-metallic element is silicon; The weight ratio of titanium to strontium is (0.1-0.3): (0.03-0.04); The method for preparing the anodized aluminum substrate is characterized in that the steps include: (1) Preheating and smelting aluminum to obtain aluminum melt; (2) adding manganese, titanium, rare earth elements, strontium and non-metallic elements into aluminum melt and stirring evenly to obtain alloy melt; (3) Degassing and heat preservation; (4) removing slag, pouring into a mold, cooling to room temperature, and obtaining an ingot; (5) subjecting the ingot to homogenization heat treatment; (6) preheating, heat-insulating, and hot-rolling the ingot obtained in step (5) to obtain an aluminum alloy coil; (7) Cooling the aluminum alloy coil to a temperature of 30-60°C, cold rolling, and annealing; (8) performing aging treatment on the annealed substrate to obtain an anodized aluminum substrate; The rare earth element is scandium; The specific implementation method of the cold rolling in step (7) is as follows: the blanking pass has a reduction of 25-30%, and a roller with a roughness of 0.5-0.8 is used for rolling; the intermediate pass has a reduction of 10-20%, and a roller with a roughness of 0.3-0.5 is used for rolling; the finished pass has a reduction of 20-30%, and a roller with a roughness of 0.1-0.3 is used for rolling; The annealing temperature is 500-520°C, and the annealing time is 10-15s; The specific implementation method of the hot rolling in step (6) is as follows: first pass: thickness before rolling is 15-20 mm, reduction is 1-2 mm, and thickness after rolling is 13-19 mm; second pass: thickness before rolling is 13-19 mm, reduction is 3-5 mm, and thickness after rolling is 8-15 mm; third pass: thickness before rolling is 8-15 mm, reduction is 5-6 mm, and thickness after rolling is 2-10 mm; The specific implementation method of the aging treatment in step (8) is: keeping the temperature at 120-200° C. for 10-15 hours.
2. The anodized aluminum substrate according to claim 1, characterized in that The smelting temperature in step (1) is 700-800°C.
3. The anodized aluminum substrate according to claim 2, characterized in that: The stirring speed in step (2) is 600-1000 r / min.
4. The anodized aluminum substrate according to claim 2, characterized in that: The specific implementation method of degassing in step (3) is: adding flux for degassing.
Citation Information
Patent Citations
A mirror-finish anodized aluminum alloy rolled sheet and its preparation method
CN108277403B
6-series alloy anode aluminum oxide board strip for mobile phone frame and preparation method of 6-series alloy anode aluminum oxide board strip
CN108913925A
Aluminum alloy and LED lamp substrate applying same
CN101591747A
Aluminum-silicon based aluminum section and preparation technology thereof
CN102747256A
Anodic oxidation aluminum alloy and preparation method thereof
CN108425046A
